Radiation-induced processes in alkali-alumina-borate glass-ceramics doped with Cr3+ ions; Journal of Non-Crystalline Solids; Vol. 534 - Valiev D. T. Damir Talgatovich; Babkina A. I. Alyona Igorevna; Zyrjyanova K. S. Kseniya Sergeevna; Nuryev R. K. Rustam Kakabaevich; Ignatjev A. I. Andrey Ivanovich; Osipova A. Yu. Anastasiya Yurjevna (2020, 2020)
Title screen